Synthesis, characterization, and surface properties of iron-doped boehmite nanofibers - Zhao, Yanyan (Langmuir : the ACS journal of surfaces and colloids, 2007)
Iron-doped boehmite nanofibers with varying iron contents have been prepared at low temperatures using hydrothermal treatment in the presence of poly(ethylene oxide) surfactant. The resulting nanofibers were characterized by transmission electron microscopy (TEM), X-ray diffraction, energy-dispersive X-ray analysis, and N2 adsorption. TEM images showed that the resulting nanostructures are predominantly nanofibers when the doped iron content is less than 5% (mol/mol); in contrast, nanosheets were formed when iron doping was above 4%. Nanotubes instead of nanofibers and iron-rich particles were observed in samples with 20% added iron. A detailed characterization and discussion on the iron-doped nanofibers is presented